Advanced aromatic organic compounds removal from refractory coking wastewater in a step-feed three-stage integrated A/O bio-filter: Spectrum characterization and biodegradation mechanism. (15th November 2022) - Hou, Zilong; Zhou, Xin; Zhao, Zilong; Dong, Wenyi; Wang, Hongjie; Liu, Huaguang; Zeng, Zhiwei; Xie, Jin
Abstract: Extensive presence of aromatic organic compounds (AOCs) is a major course for the non-biodegradability of coking wastewater (COW). In-depth understanding of bio-degradation of AOCs is crucial for optimizing the design and operation of COW biological treatment systems in practical applications. Herein, the behavior and fate of AOCs were explored in a lab-scale step-feed three-stage integrated A/O biofilter (SFTIAOB) treating synthetic COW. Long-term operation demonstrated that COD, phenol, indole, quinoline and pyridine could be simultaneously removed. Phenol and indole were chiefly removed by anoxic zones, while quinoline and pyridine removal occurred in both anoxic and aerobic zones. Ultraviolet–visible spectrum observed that initial carboxylation and subsequent ring cracking and mineralization. Infrared spectroscopy also confirmed that key functional groups were cracked and produced during AOCs bio-degradation. Three-dimensional fluorescence spectrum indicated that significant transformation and elimination of tryptophan and humic acid with high molecular weight. Ring cleavage, distinct degradation and even complete mineralization of complex AOCs were further verified by gas chromatography-mass spectrometry. Moreover, functional degrading bacteria and aromatic ring-cleavage enzymes was successfully identified. Finally, AOCs biodegradation mechanisms by alternating anoxic and aerobic treatment was unraveled. This research provides thorough insights on AOCs biodegradation using a step-feed multi-stage alternating anoxic/oxic COW treatment process. Graphical abstract: Image 1 Highlights: Aromatic organic compounds were efficiently removed by SFTIAOB. Spectrum characterization reveals functional groups, molecular structure changes of AOCs. Carboxylation, ring-cleavage and mineralization were observed during AOCs biodegradation. Specific microbes and key genes related to AOC degradation were identified. Potential AOCs biodegradation mechanisms under alternating anoxic/oxic were proposed.